Understanding Helicobacter pylori Infection Prevalence and Associated Factors in slum and swampy areas of Narayanganj, Bangladesh: Findings from Medical Camps - Jarin, Ismath; Ahmed, Tawsif; Nahar, Jamila Jannatun (Brac University, 2024)
A thesis submitted to the Department of Mathematics And Natural Science in partial fulfillment of the requirements for the degree of B.Sc. in Microbiology, 2024.